2001
DOI: 10.1128/jb.183.7.2384-2388.2001
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Transposition System for Efficient Generation of Random Mutants of Campylobacter jejuni

Abstract: Campylobacter jejuni is the most common cause of food-borne illnesses in the United States. Despite the fact that the entire nucleotide sequence of its genome has recently become available, its mechanisms of pathogenicity are poorly understood. This is in part due to the lack of an efficient mutagenesis system. Here we describe an in vitro transposon mutagenesis system based on the Staphylococcus aureus transposable element Tn552 that allows the efficient generation of insertion mutants of C. jejuni. Insertion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…not been well characterized, although several recent transposon mutagenesis experiments have demonstrated that Cj0041, Cj0062c, and Cj1026 are required for motility (17,29,50). For Cj1026 and Cj0062c, these motility defects may be caused by polar effects on the transcription of the downstream genes: flgR ( 54 activator) and fliA ( 28 ), respectively.…”
Section: Levels Of Genes Encoding Specific Flagellar Transcripts and mentioning
confidence: 99%
“…not been well characterized, although several recent transposon mutagenesis experiments have demonstrated that Cj0041, Cj0062c, and Cj1026 are required for motility (17,29,50). For Cj1026 and Cj0062c, these motility defects may be caused by polar effects on the transcription of the downstream genes: flgR ( 54 activator) and fliA ( 28 ), respectively.…”
Section: Levels Of Genes Encoding Specific Flagellar Transcripts and mentioning
confidence: 99%
“…1). Recently, successful and efficient transposon mutagenesis (90,91) has breached one of the early barriers to the explication of C. jejuni molecular pathogenesis. Together with the genomic sequence, which will provide the cornerstone for powerful novel techniques such as microarray and protein expression methodologies, these developments herald a renaissance period for Campylobacter research that can be expected to continue for some time.…”
Section: It Is Not Yet Clear What Role Cdt Plays In Infection In Vivomentioning
confidence: 99%
“…Also present in this organism is CheA, which contains both an HK domain and an RR domain. We did not generate a cheA mutant as the role of this gene in chemotaxis and motility (11,18,21) is well established. We were successful in generating mutants with mutations in 9 of the 11 RRs (Table 2).…”
Section: Generation Of Rr Mutantsmentioning
confidence: 99%